A Hybrid Model for Post-Divorce Child Support Enforcement: Comparative Insights and Legal Reform - Setiyowati Setiyowati; Lê Hồ Trung Hiếu (APPTHI, 2026)
The enforcement of post-divorce child support rights remains a significant challenge in Indonesia. Despite legal provisions under Law Number 1 of 1974 on Marriage, the Compilation of Islamic Law (KHI), and Law Number 35 of 2014 on Child Protection, compliance with child support obligations remains low due to the absence of an effective enforcement mechanism. This study aims to analyze the weaknesses of Indonesia’s child support enforcement system, examine comparative practices in the United States, Singapore, Japan, and China, and formulate an enforcement model suitable for Indonesia. Using a normative-juridical approach combined with an international comparative method, the study evaluates child support systems through five analytical parameters: legal basis, implementing institutions, sanction mechanisms, information systems, and compliance levels. The findings reveal that effective enforcement systems consistently rely on specialized institutions, integrated information systems, and graduated sanctions. Based on these findings, this study proposes a Hybrid Child Support Enforcement Model supported by the Child Support Enforcement Agency (BPNA) and the Integrated Child Support Information System (SINAT) as its primary innovations. The model offers a practical framework for strengthening child rights protection and improving compliance with child support obligations in Indonesia.